2017
DOI: 10.1037/ser0000161
|View full text |Cite
|
Sign up to set email alerts
|

Factors impacting rural Pacific Island veterans’ access to care: A qualitative examination.

Abstract: Pacific Island veterans suffer from greater severity of posttraumatic stress disorder (PTSD) compared with Caucasian veterans but face substantial barriers to mental health care. However, the factors that may dissuade or facilitate veterans in the Pacific Islands from seeking mental health care are not known. The main aim of this study was to identify how internal and external factors interact to impact wounded warriors' access to and use of mental health services. Veterans residing in 5 rural Pacific Island l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…In addition to primary care veterans, another group who may encounter additional barriers to care is rural veterans. In qualitative studies, rural veterans have described self‐reliance, stigma, problems with treatment navigation, and lack of trust in providers as barriers to care, whereas perceived need for care, support from other veterans, warm hand‐offs from medical to mental health providers, and continual access to providers served as facilitators (Fischer et al., ; Whealin, Nelson, Kawasaki, & Mahoney, ). It is unknown if treatment barriers and facilitators differ between rural and urban primary care patients with PTSD.…”
mentioning
confidence: 99%
“…In addition to primary care veterans, another group who may encounter additional barriers to care is rural veterans. In qualitative studies, rural veterans have described self‐reliance, stigma, problems with treatment navigation, and lack of trust in providers as barriers to care, whereas perceived need for care, support from other veterans, warm hand‐offs from medical to mental health providers, and continual access to providers served as facilitators (Fischer et al., ; Whealin, Nelson, Kawasaki, & Mahoney, ). It is unknown if treatment barriers and facilitators differ between rural and urban primary care patients with PTSD.…”
mentioning
confidence: 99%
“…The participation of indigenous minority soldiers in combat is a neglected research area, although, recently, the challenging and complex needs of soldiers, who belong to these groups, are gaining recognition (McDonald, 2017; Whealin, Nelson, Kawasaki, & Mahoney, 2017). Updated research emphasizes the importance of identifying the unique cultural protective and risk factors (O’Keefe & Reger, 2017) for the development of culturally adapted treatment interventions (Whealin, Yoneda, et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicated that there were a high number of untreated veterans with PTSD in rural locales. To gain firsthand knowledge of the clinical needs and preferences of these veterans, qualitative data were collected via focus groups with veterans of from all war eras and their family members (Whealin, Nelson, Kawasaki, & Mahoney, 2017). Representative rural locations were targeted on four Hawaiʻian islands, as well as in U.S. territories of the Western Pacific and Northern Marianas Islands.…”
Section: Stage I: Assessmentmentioning
confidence: 99%
“…Representative rural locations were targeted on four Hawaiʻian islands, as well as in U.S. territories of the Western Pacific and Northern Marianas Islands. Nine focus groups were also held with Veteran family members (Whealin, Nelson & Kawasaki, 2017). Focus group data revealed a strong need for basic education about coping with PTSD for both veterans and family members.…”
Section: Stage I: Assessmentmentioning
confidence: 99%